THE EFFECT OF THE USE OF SCRUB, CONSUMPTION OF TRADITIONAL HERBAL AND EXCLUSIVE BREASTFEEDING WITH THE DEVELOPMENT OF UNDERAGE INFANTS FROM 12 MONTHS IN MADURA COMMUNITY, EAST JAVA - Nurul Kamariyah; Siti Nurjanah (Nurse and Health: Jurnal Keperawatan, 2021)
Background: The tradition that is still attached to the Madura community even though they have received higher education is to maintain the culture of their ancestors which is perceived to be true, restricted movement, use of body scrubs, drinking herbal medicine, and giving food to babies early. This will continue to be implemented by their children and grandchildren as long as the problem is believed to be the best tradition (Kamariyah, 2019). Objectives: The purpose of this research was to analyze the effect of using scrubs, consumption of herbs, and exclusive breastfeeding with the development of infants less than 12 months in the Madura community of East Java. Methods: This research used analytical research design. the population is postpartum mothers and infants under the age of 12 months in the Madura community, East Java, with population of 30 people, a sample of 26 respondents simple random sampling. The independent variables are the use of scrubs, consumption of herbal medicine, and exclusive breastfeeding, while the dependent variable is infant development. Data collection was done by means of interviews and observations, and the analysis of the data used was the Mann-Whitney test. The results of the Mann-Whitney statistical test with significance level 0.05. Results: The result was 0.002 < ? 0.05 so that H0 was rejected, which means that there is an influence of the tradition of consuming herbal medicine with the breastfeeding, the result is 0.022<0.05 so that H0 is rejected, which means that there is an influence of the tradition of exclusive breastfeeding. with the development of infants aged less than 12 months in the Madurese community of East Java. Conclusion: Consumption of herbal medicine, use of scrubs and exclusive breastfeeding will increase the development of infants before the age of 12 months in the Madurese community of East Java. Conclusion: Expected to apply the existing culture while still paying attention to the science that develops according to its era, for health workers to disseminate the knowledge obtained and change the mindset of the community.